Historyczne podziały Europy a społeczno-gospodarcze uwarunkowania postaw kulturowych wobec bankowości w Polsce - Kurkliński, Lech (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
This paper is devoted to the presentation of the significance of the historicaldivisions in Europe for the formation of the socio-economic conditions for thedevelopment of the banking sector in Poland. The paper presents four main divisionsrelated to the functioning of the Roman Empire and Barbaricum, Latin andByzantine Europe, the dualism of the economic development of Europe fromthe sixteenth century and the creation of the capitalist and socialist blocks afterthe Second World War, and their relations to the position of Poland. Historicaloverview is juxtaposed with the current shape of the Polish banking sector, andespecially the dominance of banks controlled by foreign capital. This confrontationis primarily intended to indicate the importance of cultural factors for thedevelopment of the banking sector.